Do immunosuppressive treatments influence immune responses against adenovirus-based COVID-19 vaccines in patients with multiple sclerosis? An Argentine multicenter study - Silva, Berenice Anabel; Miglietta, Esteban; Casabona, Juan Cruz; Wenker, Shirley; Eizaguirre, María Bárbara; Alonso, Ricardo; Casas, Magdalena; Lázaro, Luciana Grimanesa; Man, Federico; Portuondo, Gustavo; Lopez Bisso, Abril; Zavala, Noelia; et al. (Frontiers in Immunology, 2024)
There are no reports in LATAM related to longitudinal humoral and cellular response to adenovirus based COVID-19 vaccines in people with Multiple Sclerosis (pwMS) under different disease modifying therapies (DMTs) and neutralization of the Omicron and Wuhan variants of SARS-COV-2. IgG anti- SARS-COV-2 spike titer were measured in a cohort of 101 pwMS under fingolimod, dimethyl fumarate, cladribine and antiCD20, as well as 28 healthy controls (HC) were measured 6 weeks after vaccination with 2nd dose (Sputnik V or AZD1222) and 3nd dose (homologous or heterologous schedule). Neutralizing capacity was against Omicron (BA.1) and Wuhan (D614G) variants and pseudotyped particles and Cellular response were analyzed. Multivariate regression analysis showed anti-cd20 (β= -,349, 95% CI: -3655.6 - -369.01, p=0.017) and fingolimod (β=-,399, 95% CI: -3363.8 - -250.9, p=0.023) treatments as an independent factor associated with low antibody response (r2 adjusted=0.157). After the 2nd dose we found a correlation between total and neutralizing titers against D614G (rho=0.6; p<0.001; slope 0.8, 95%CI:0.4-1.3), with no differences between DMTs. Neutralization capacity was lower for BA.1 (slope 0.3, 95%CI:0.1-0.4). After the 3rd dose, neutralization of BA.1 improved (slope: 0.9 95%CI:0.6-1.2), without differences between DMTs. A fraction of pwMS generated anti-Spike CD4+ and CD8+ T cell response. In contrast, pwMS under antiCD20 generated CD8+TNF+IL2+ response without differences with HC, even in the absence of humoral response. The 3rd dose significantly increased the neutralization against the Omicron, as observed in the immunocompetent population. Findings regarding humoral and cellular response are consistent with previous reports.